Cover Feature: Structure and Orientation of Water and Choline Chloride Molecules around a Methane Hydrophobe: A Computer Simulation Study (ChemPhysChem 21/2022). Issue 21 (4th November 2022) - Nanavare, Pooja; Choudhury, Asha Rani; Sarkar, Soham; Maity, Atanu; Chakrabarti, Rajarshi
Abstract : The Cover Feature illustrates the distribution of the different components of aqueous choline chloride solution around the hydrophobe methane. The hydrogen bonds formed between water molecules, choline cations, and chloride ions are shown using light yellow dots. The preferred orientations of water with respect to methane at different distances from the latter are quantified in a 2D histogram. More information can be found in the Research Article by Rajarshi Chakrabarti and co‐workers .